A review on the tooling technologies for composites manufacturing of aerospace structures: materials, structures and processes - Li, Yong; Xiao, Yao; Yu, Long; Ji, Kang; Li, Dongsheng (Composites. Part A, Applied science and manufacturing, 2022)
Tools play key roles in determining the accuracy, performance and cost of composites structures manufacturing. The increasing desire in performance of composites components has required the close cooperation between industrial and academic sides to utilise and explore new developments in materials, structures and manufacturing technologies of tools, so as to provide lightweight, low cost, durable and functional tools for manufacturing high performance composites structures. Hence, this paper provides a review of the main solutions of tooling technologies development for composites in aerospace industry, trying to mediate the current gap between industry and academy. The progress in materials, structures and functionalities of tools for conventional and advanced composites manufacturing has been explored. The key and advanced manufacturing processes for tools have been reviewed. Finally, conclusions on the state-of-art and future trends of tooling technologies have been given, providing a guidance for tool design and manufacturing for advanced composites structures.